2021
DOI: 10.1007/s00262-021-03090-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical determinants of long-term survival in metastatic uveal melanoma

Abstract: This study aimed to identify prognostic factors in patients with metastatic uveal melanoma (UM) that were associated with long-term survival in a real-world setting. A total of 94 patients with metastatic UM were included from German skin cancer centers and the German national skin cancer registry (ADOReg). Data were analyzed for the response to treatment, progression-free survival, and overall survival (OS). Prognostic factors were explored with univariate Cox regression, log-rank, and χ2-tests. Identified fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 39 publications
2
20
1
2
Order By: Relevance
“…The OS of 11.9 months is lower compared to previous retrospective studies, in which OS was 16 and 22.3 months in a real-world setting when treatment with ICB was available [4,5]. These data suggested that the prognosis of patients with advanced UM has improved due to the availability and more frequent use of ICB [4,5,9,13]. The lower OS in this collective is probably due to a relatively delayed treatment start, in particular in cohort A as the re-induction with ICB preferably occurred in later treatment lines.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…The OS of 11.9 months is lower compared to previous retrospective studies, in which OS was 16 and 22.3 months in a real-world setting when treatment with ICB was available [4,5]. These data suggested that the prognosis of patients with advanced UM has improved due to the availability and more frequent use of ICB [4,5,9,13]. The lower OS in this collective is probably due to a relatively delayed treatment start, in particular in cohort A as the re-induction with ICB preferably occurred in later treatment lines.…”
Section: Discussioncontrasting
confidence: 58%
“…We detected a median OS of 11.9 months (95% CI 9.4-15.6) and a median PFS of 2.5 months (95% CI 2.2-3) to any ICB for the entire cohort. The OS of 11.9 months is lower compared to previous retrospective studies, in which OS was 16 and 22.3 months in a real-world setting when treatment with ICB was available [4,5]. These data suggested that the prognosis of patients with advanced UM has improved due to the availability and more frequent use of ICB [4,5,9,13].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…A prognostic score for patients with MUM, including the variables time to metastatic diagnosis, presence of bone metastases, and LDH, was recently developed [ 41 , 42 , 43 ]. Based on the results of our analysis, the parameters age (cut-off: ≥55 years), as well as LDH, S100, and NLR (cut-off: 3.5), should be considered in case of prognosis assessment.…”
Section: Discussionmentioning
confidence: 99%